Bandagem elástica no músculo trapézio em adultos saudáveis - Silva, Andréa Pereira da (2015)
The elastic bandage as therapeutic instrument is a resource already in use for long time in areas such as Physiotherapy, but has only recently started to gain ground in the Speech Language Pathology for both clinic use and research. It has been used as auxiliary treatment for a number of musculoskeletal dysfunctions in the field of orofacial motility with excellent clinic results. Its application is diversified and, according to a clinical and therapeutic evaluation, can be used to increase or decrease the neuron excitement of a muscle. Despite of the elastic bandage vast usage possibility, it s use in Speech Language Pathology is still empiric once there are so few studies about this theme. Objective: to verify the elastic bandage effect on healthy adult s trapezius muscle through surface electromyography and a qualitative questionnaire. Method: 51 healthy adults participated from 20 to 35years old, 21 male and 30 divided randomly into three groups: G1 Group with tensioned elastic bandage, G2 Group with non-tensioned elastic bandage and G3 Control group that did no use the elastic bandage. For the data as acquisition a pre-bandage, with-bandage and 24h-after-bandage electromyography evaluations were performed on G1 and G2 subjects. For both groups was also applied a questionnaire. For the G3 subjects two electromyography evaluations were performed with a 24hour interval. The resulting data was loaded to an Excel spreadsheet where statistic crosses were performed considering the stages within the groups and crossing between groups. Results: There were no significant differences on the electromyography data during the tasks Rest (R) and maximum voluntary contraction (MVC) in any groups, immediately after placing the bandage and after 24hours on the groups that used this resource. Comparing G1, G2 and G3 there wasn t any evidence of significant differences on analyzed variables. Confronting G1 and G2 during the pre-bandage and with-bandage stages difference was found only during the left side MVC. In the questionnaire, the most part of the G1 group reported a relaxing sensation during sleep. Conclusion: The sample subjects that used the elastic bandage did not show significant result on the electromyographic signal of the evaluated muscle. However, regarding the self-reported questionnaire a big part of the subjects that used the bandage tape affirmed having a relaxing feeling